MINAT SISWA TERHADAP PEMBELAJARAN SENI BUDAYA KELAS VII 4 SMP 1 KOTO XI TARUSAN - Sari, Dezya Kumala; Yensharti, Yensharti (SENDRATASIK UNP, 2019)
AbstractÂ The type of studywas qualitative with using a descriptive analysis approach. The object of this study wasthe students of class VII 4. The instrument used in this study was the researcher as the main researcher and it was assisted by additional instruments such as a set of stationery and a photo camera. Techniques ofdata collection were doneby some ways such as doing literature study, observation, interview, and documentation. Meanwhile Techniques of data analysis were done by classifying primary and secondary data, and it was arranged systematically. The result shows that the students' interest in learning cultural artsin SMP N 1 Koto XI Tarusan is still relatively low. This is due to the way that the teacher in teaching is tedious, lack of motivation and encouragement, the teacher still uses the lecture method, as well as the factors that influence students' interest in learning cultural arts in SMP N 1 Koto XI Tarusan, namely 1) Internal factor (in students) which includes concentration and awareness of student learning. 2) External factors (outside of students) which includes teachers, family, environment and school factors.Â Keywords: interests, students, cultural artsÂ